Penerapan Smart Sukuk Ijarah Berbasis Wakaf Untuk Pengembangan Harta Wakaf - Fandra, Julianto (AL-ITTIFAQ Jurnal Ekonomi Syariah, 2025)
This study focuses on presenting a working model by combining the concept of Waqf and smart Sukuk working on the basis of Ijarah contract. In a study it was found that due to several reasons such as supervision and lack of transparency in waqf administration, Waqf has lost much of its dynamism. Due to these and several other reasons, many waqf properties are neglected or in a dilapidated condition, which has led to the effectiveness and role of Waqf being scrutinized. There is a need to widely advertise the important role played by Waqf as an instrument of social welfare. Therefore, this model is suggested for the development of waqf properties and to revive the role of waqf in the social welfare of the community. Using qualitative methods, this paper also highlights the issues or challenges involved in the practical implementation of smart Sukuk or Ijarah contract, including possible Shariah issues. The policy implications of this paper suggest that countries adopt this technologically advanced and Shariah compliant working model to target issues related to waqf property development. This paper will also offer a broader perspective on smart Sukuk to existing and upcoming professionals in the field of Islamic finance and hopefully encourage them to develop a beneficial framework for smart Sukuk and other smart contracts, which is currently lacking